We'll always have McDonald's: Between poetic topos and advertising topic - Bagué Quílez, Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article deals with the relevance of McDonald’s brand in recent Spanish poetry. As other franchises, McDonald’s not only designates a specific space, but can also be understood as a polysemic symbol linked to the evanescence of contemporary places. The analyzed texts show that the mention of this burger chain in current poetry can activate different semantic frameworks: a message of social criticism, a reflection on the manipulation of advertising rhetoric, a dialogue with classical culture or a metadiscursive meditation. From a more general perspective, the allusion to certain trademarks allows updating topics belonging to the literary tradition (locus amoenus, carpe diem, memento mori) and establishing new topics arising from the advertising background and reflected with ironic distance (the fetishist celebration of merchandise, the invitation to instant happiness, the democratizing power of consumerism).
Keywords: Literary topos; advertising topic; McDonald's; Spanish contemporary poetry